How to choose the duration of antibiotic therapy in patients with pneumonia. Issue 2 (April 2015) - Aliberti, Stefano; Giuliani, Fabio; Ramirez, Julio; Blasi, Francesco
Abstract : Purpose of review: The appropriate duration of antimicrobial treatment in patients with pneumonia remains a matter of controversy. The purpose of this article is to review different approaches that have been used to determine the duration of antimicrobial therapy mainly driven either by the antibiotic chosen, isolated pathogen, host characteristics, or severity of the disease. Recent findings: When considered individually, every approach has strengths and weaknesses. Targeting the duration of antibiotic therapy based on a single biomarker, such as procalcitonin, is a promising approach that showed a reduction in antibiotic exposure in different settings, diseases, and study populations. Furthermore, an individualized approach according to time to reach clinical stability takes into account all the previous cited factors and may be another feasible and effective strategy to determine the most appropriate duration of the antibiotic therapy in patients with pneumonia. Summary: A shorter duration of antibiotic course based on response to treatment may be favorable in patients with pneumonia due to a potential reduction of adverse events and antibiotic resistance, the opportunity to enhance patients' compliance and to decrease healthcare costs.